General and ICT Self-Efficacy in Different Participants Roles in Cyberbullying/Victimization Among Pakistani University Students - Musharraf, Sadia; Bauman, Sheri; Anis-ul-Haque, Muhammad; Malik, Jamil Ahmad (Frontiers in Psychology, 2019)
The study examines both general and Internet and Communication Technology (ICT) self-efficacy in cyber-victims, cyber-bullies, and cyber bully-victims in comparison to un-involved students. Gender differences were also examined. A total of 1115 Pakistani university students from six universities participated in the study. Analyses were conducted on 950 complete cases (371 males, and 579 females). Data were collected on cyberbullying/victimization, general self-efficacy, ICT self-efficacy, traditional bullying/victimization, ICT usage, social desirability, and demographics. Multinomial logistic regression analysis indicated that ICT self-efficacy significantly decreased the probability of being a cyber-victim and significantly increased the chances of being a cyber-bully whereas general self-efficacy appeared to have no role in predicting participant roles in cyberbullying after controlling for covariates (i.e., age, gender, traditional bullying, traditional victimization, social desirability, Internet usage, time spent on the Internet, and social networking sites-SNS). Findings of the study have important implications for developing and enhancing interventions with respect to the inclusion of ICT related skills in anti-cyberbullying programs. With respect to gender, findings showed that females reported a higher level of victimization while males reported higher perpetration on both traditional and cyberbullying.